ANALYSIS OF THE IMPLEMENTATION OF THE VALUES OF PATIENCE AND TAWAKAL IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT STATE MIDDLE SCHOOL 04 PEMULUTAN - Feriansyah; Alihan Satra; Muhammad Erpan Hakim; Dwi Rahma Yanti; Khairin Sazkia Fawaza; Nadia Amilia (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the understanding of eighth grade students towards the values ​​of patience and trust in Allah SWT contained in QS . Al -Baqarah Verse 153 and its relevance in building the character of adolescents at SMP Negeri 04 Pemulutan . The verse contains an important message about the command to be patient , pray , and believe in Allah SWT's help in facing various life tests . These values ​​are very relevant for eighth grade students who are entering the early phase of adolescence , where they face various emotional , social , and academic challenges . The study used a descriptive qualitative method with data collection techniques through written tests , in-depth interviews , and direct observation . The subjects of the study were 20 eighth grade students of SMP Negeri 04 Pemulutan . The results showed that students ' understanding of the meaning of QS. Al-Baqarah Verse 153 was in the fairly good category . Most students were able to identify the main values ​​of patience and trust in Allah SWT and relate them to everyday life . However , there were still a small number of students who had not optimally internalized and applied these values ​​in their behavior . daily life . The main inhibiting factors are the lack of real-life examples from the environment and minimal habituation . This study concludes that QS. Al-Baqarah Verse 153 has great potential as a medium for character formation in adolescents . Therefore , a more interactive learning approach is needed and an increased role of teachers as primary role models in exemplifying the values ​​of patience and trust in God to students .